Drug Repurposing for Monkeypox: An Alternative Strategy for Emergency Response - Luthfi Harbulcholizi; Jekmal Malau; Ihsan Alfiandri; Iqbal Zulkifli; Ratika Rahmasari (Universitas Sebelas Maret, 2025)
The global monkeypox (MPOX) outbreak, which has resulted in more than 100,000 confirmed cases across over 120 countries, underscores the urgent need for effective therapeutic strategies. MPOX, caused by a virus belonging to the Orthopoxvirus genus, poses significant clinical and public health challenges, particularly in regions with limited healthcare capacity. Although the World Health Organization declared MPOX a Public Health Emergency of International Concern in 2022, no specific antiviral treatment has yet been formally approved. While vaccination remains essential for long-term prevention, its impact is constrained by limited availability and unequal global distribution. Consequently, drug repurposing has emerged as a practical, rapid, and cost-efficient strategy to address immediate therapeutic demands during active outbreaks. This narrative review evaluates key repurposed antiviral agents including tecovirimat, brincidofovir, and cidofovir were originally developed for other Orthopoxvirus infections. A structured literature search using PubMed, ScienceDirect, and Google Scholar (2014–2024) identified studies providing clinically relevant evidence regarding their therapeutic roles in MPOX. Tecovirimat demonstrated consistent potential to improve viral clearance, shorten symptom duration, and reduce severe manifestations. Brincidofovir exhibited a more favorable safety profile, albeit with limited clinical data, whereas cidofovir showed antiviral activity but remains restricted by its nephrotoxicity. Collectively, current evidence suggests that drug repurposing offers a timely and resource-efficient option for managing MPOX and mitigating disease burden while vaccine accessibility continues to vary globally. When integrated with targeted public health interventions, repurposed drugs may serve as a crucial interim strategy to reduce transmission and enhance outbreak response capacity.